1988
DOI: 10.1084/jem.168.4.1403
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cell wall-induced immunosuppression. Role of transforming growth factor beta.

Abstract: Group A streptococcal cell wall (SCW)-injected rats exhibit a profound immunosuppression that persists for months after the initial intraperitoneal injection of SCW. The goal of this study was to determine the mechanisms for the suppressed T lymphocyte proliferative responses in this experimental model of chronic inflammation. When spleen cell preparations were depleted of adherent cells, restoration of T cell proliferative responses to Con A and PHA occurred, implicating adherent macrophages in the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 32 publications
3
33
0
2
Order By: Relevance
“…Suppression ofhuman IFN-y biological activity (24) and gene expression (11) has very recently been attributed to a similarly autoinducible lymphokine, TGF/3 . It has been shown that TGF-/3 is an immunosuppressive cytokine produced by rat macrophages (25). We have recently identified TGF0 in a murine MLR supernatant and shown it to be a physiologic downregulator of murine IFN-y gene expression (26).…”
Section: Resultsmentioning
confidence: 99%
“…Suppression ofhuman IFN-y biological activity (24) and gene expression (11) has very recently been attributed to a similarly autoinducible lymphokine, TGF/3 . It has been shown that TGF-/3 is an immunosuppressive cytokine produced by rat macrophages (25). We have recently identified TGF0 in a murine MLR supernatant and shown it to be a physiologic downregulator of murine IFN-y gene expression (26).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to modulating FcyRIII expression, TGF-f is a potent inhibitor of immunologic functions in vitro and in vivo (25,(46)(47)(48)(49), and it is possible that enhanced levels ofTGF-,3 in patients with AIDS may also contribute to the immunosuppressed state of these individuals. T and B lymphocytes produce TGF-f3 when stimulated (50,51), as do cells of monocyte lineage (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Lewis rats were injected on day 0 with SCW and their Al determined daily thereafter. On day 10, half of the animals (filled circles) were begun on a daily dosing regimen of 5 ,ug TGFfl/animal (i.p.). Joint scores for control animals were as indicated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…TGF,B has been shown in vitro to inhibit proliferation of thymocytes (1), T and B lymphocytes (2)(3)(4)(5), and the less differentiated hematopoietic progenitor cells (6)(7)(8)(9). In addition, it suppresses B cell production of IgG and IgM (2) and antagonizes the immunoregulatory effects ofinterleukins-1, -2, and -3 (2-4, 10), colony stimulating factors (8,10), and interferons alpha ( 11) and gamma (12).…”
Section: Introductionmentioning
confidence: 99%